EFFECT OF TRAINING ON KNOWLEDGE OF EXTENSION PERSONNEL IN SELECTED AGRICULTURAL VALUE CHAINS IN OGUN STATE, NIGERIA - OLAOYE, O.J.; OJEBIYI, W.G.; ANAKWE, E.; AKINNIYI, O.T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study examined the effect of Federal Ministry of Agriculture and Rural Development (FMARD) training on extension personnel's knowledge of selected agricultural value chains in Ogun State, Nigeria. All 40 extension personnel participating in the FMARD training held at the Ogun State ADP Headquarters, Abeokuta, were selected for this study. The questionnaire was designed to collect data from the extension personnel. Collected data were subjected to descriptive and inferential analytical techniques. Results revealed that the majority (72.5%) of the participants were from Ogun ADP. Extension service delivery was dominated by males (62.5%), aged 31-40 years (57.5%), married (82.5%), had HND/B.Sc (82.5%), and studied agriculture-related courses (90.0%). Almost all (95.0%) of the extension personnel positively perceived the FMARD training. Knowledge gain was highest in extension service delivery (66.5%) and least in vegetable production (46.5%). The majority (85.0%) indicated they needed more training in the future. The training needs were primarily in the areas of crop production (52.9%), livestock production (50.0%) and fisheries (20.6%). It was revealed that there were significant differences in the pre and post-training knowledge of extension personnel in extension (t=9.962), livestock (t=10.811), vegetable production (t=9.595), and maize production (t=8.486) at p≤0.01. It was also revealed that extension personnel generally had significantly higher knowledge after the training. The study concluded that the FMARD training positively affected extension personnel's knowledge of the different agricultural value chains. It was recommended that more training should be organized by the FMARD for extension personnel, especially on the livestock production and fisheries value chains.